2001
DOI: 10.1016/s0893-133x(01)00266-4
|View full text |Cite
|
Sign up to set email alerts
|

Vigabatrin Decreases Cholecystokinin-Tetrapeptide (CCK-4) Induced Panic in Healthy Volunteers

Abstract: Vigabatrin increases gamma aminobutyric acid (GABA) levels by irreversible inhibition of the GABA-catabolizing enzyme GABA-transaminase (GABA-T). Preclinical studies suggest anxiolytic effects in vigabatrin treated rats. Anxiolytic effects in patients with panic disorder (PD) could therefore be expected. To evaluate putative anxiolytic properties of vigabatrin in humans, CCK-4-induced panic symptoms were studied in healthy volunteers before and after vigabatrin treatment. After placebo-controlled administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
1
3

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 27 publications
5
28
1
3
Order By: Relevance
“…Similarly, in a prior study we observed a blunted HPA system response after selective GABAergic treatment with vigabatrin in healthy volunteers (-'-)) and the placebo group (PLC 1 (-J-) and PLC 2 (-K-)). (Zwanzger et al, 2001). Both findings are congruent with several preclinical and clinical data showing an inhibition of the HPA-axis activity after treatment with benzodiazepines.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Similarly, in a prior study we observed a blunted HPA system response after selective GABAergic treatment with vigabatrin in healthy volunteers (-'-)) and the placebo group (PLC 1 (-J-) and PLC 2 (-K-)). (Zwanzger et al, 2001). Both findings are congruent with several preclinical and clinical data showing an inhibition of the HPA-axis activity after treatment with benzodiazepines.…”
Section: Discussionsupporting
confidence: 86%
“…Administration of vigabatrin, an inhibitor of the GABA-transaminase, in 10 healthy volunteers significantly attenuated symptoms provoked by CCK-4. Reductions of the API score by 45% and of the PSS score by 54% were observed after vigabatrin treatment (Zwanzger et al, 2001). This effect size is similar to the results after alprazolam treatment in the current study.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations